On the diffraction of sound wave by a wedge - WYRZYKOWSKI, Roman; SNAKOWSKI, Jan K. (Archives of Acoustics, 1982)
This paper presents calculations for plane wave diffraction by a right-angled wedge. Using the UFIMTSEV and OBERHETTINGER's theoretical approach, formulae are obtained for the diffracted field potential on the shaded wall of the wedge in the form of a series of cylindrical functions and a real integral. Some results of numerical calculations are also presented.